Estimate of Errors of Processing of Parts from Tough Titanium Alloys (Texas Journal of Engineering and Technology, 2022)
The article covers the analysis of components of the cutting errors before choosing the type of control and presents a model of processing error based on analysis of reasons that cause deviation from linear dimensions during machining.